Long-term impact of adenotonsillectomy on the quality of life of children with sleep-disordered breathing - Sousa Caixeta, Juliana Alves; Silva Sampaio, Jessica Caixeta; Costa, Vanessa Vaz; Bruno da Silveira, Isadora Milhomem; Fernandes de Oliveira, Carolina Ribeiro; Alves Sousa Caixeta, Luiz Claudio [UNESP]; Gomes Avelino, Melissa Ameloti (Thieme, 2021)
Introduction Adenotonsillectomy is the first-line treatment for obstructive sleep apnea secondary to adenotonsillar hypertrophy in children. The physical benefits of this surgery are well known as well as its impact on the quality of life (QoL), mainly according to short-term evaluations. However, the long-term effects of this surgery are still unclear. Objective To evaluate the long-term impact of adenotonsillectomy on the QoL of children with sleep-disordered breathing (SDB). Method This was a prospective non-controlled study. Children between 3 and 13 years of age with symptoms of SDB for whom adenotonsillectomy had been indicated were included. Children with comorbities were excluded. Quality of life was evaluated using the obstructive sleep apnea questionnaire (OSA-18), which was completed prior to, 10 days, 6 months, 12 months and, at least, 18 months after the procedure. For statistical analysis, p-values lower than 0.05 were defined as statistically significant. Results A total of 31 patients were enrolled in the study. The average age was 5.2 years, and 16 patients were male. The OSA-18 scores improved after the procedure in all domains, and this result was maintained until the last evaluation, done 22 ± 3 months after the procedure. Improvement in each domain was not superior to achieved in other domains. No correlation was found between tonsil or adenoid size and OSA-18 scores. Conclusion This is the largest prospective study that evaluated the long-term effects of the surgery on the QoL of children with SDB using the OSA-18. Our results show adenotonsillectomy has a positive impact in children’s QoL.
Keywords: Adenoidectomy; Child; OSA-18; Quality of life; Sleep-disordered breathing; Tonsillectomy